Numerical analysis of stress distribution in offshore wind turbine M72 bolted connections - Redondo, Raquel; Mehmanparast, Ali (MDPI, 2020)
The use of bolted joints to connect the transition piece and monopile is nowadays widely applied in the offshore wind industry. Traditionally, grouted connections were used in the early generation of offshore wind turbines, but the experienced failures in such connections led to an increased tendency towards bolted flange connections to join the transition piece and monopile in the new generation of offshore wind turbines. The bolts used for this purpose have high strength and huge sizes, and are subjected to a preload that is applied during the tightening process. The present study is focused on the analysis of preload effects on stress distribution in M72 bolted connections by considering different friction coefficients between the bolt and nut threads. The bolt is considered to be made of grade 10.9 steel, whereas the nut is assumed to be made of grade 8.8 steel, which is a softer material. Using the finite element commercial software package Abaqus, numerical models were developed and analysed to establish trends for stress distribution and plastic strains during the bolt tightening process, and to quantify stress concentration factors in individual engaged threads
Keywords: MP-TP connection; M72 bolts; bolted connections; preload; offshore wind